Effect of Fiber's Interfaces Cohesive Strength in Unidirectional Fibrous Structural Material on SIF and Fracture Energy. Issue 5 (19th December 2013) - Borovik, Alexandra V.; Borovik, Valery G.; Zschech, Ehrenfried
<x xml:space="preserve">Abstract</x> This paper presents the study of the effect of inelastic shear stress at the interface between the fibers on the SIF and energy absorbed at the initial stages of the fracture of the material with unidirectional fibrous structure. The dependence between the energy absorbed by the deformation of the fiber with a crack, and the cohesive strength of the interface has a domed form with a well‐defined maximum. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>